High strength gelatin-based nanocomposites reinforced by surface-deacetylated chitin nanofiber networks. (1st September 2018) - Chen, Chuchu; Wang, Yiren; Yang, Yini; Pan, Mingzhu; Ye, Ting; Li, Dagang
Highlights: Surface deacetylation lead to the mostly individualized chitin nanofiber (S-ChNF). S-ChNF/gelatin nanocomposite was fabricated using immersion method. S-ChNF preserved interconnected nanonetwork structures in the gelatin matrix. S-ChNF/gelatin exhibited high transmittance of around 89% at 600 nm wavelength. S-ChNF/gelatin possessed significantly improved mechanical properties than gelatin. Abstract: In this study, chitin nanofiber (ChNF) was deacetylated on the crystalline surface by NaOH treatment, leading to the fibrillation of mostly individualized nanofibers with high aspect ratio. The small diameter and high strength of chitin nanofibers make them promising reinforcing fillers for composites. Herein by introducing into the gelatin, surface-deacetylated chitin nanofiber (S-ChNF)/gelatin nanocomposites were fabricated in different component ratios using immersion method followed with drying. Due to the reinforcing effect attributed to S-ChNF, mechanical properties of the S-ChNF/gelatin were significantly improved in both stress and Young's modulus while still maintaining high transparency regardless of nanofiber content. Morphology and Fourier-transform infrared characterization revealed that S-ChNF preserved nanonetwork structures in the gelatin matrix and exhibited good compatibility through hydrogen bonding, which further confirmed the improvement in mechanical properties. Therefore, these S-ChNF/gelatin nanocomposites based on biocompatible and biodegradable raw materials have potential applications in biomedical and food packaging industries.